The Effectiveness of Martial Arts Interventions in Autism Spectrum Disorder: A Scoping Review - Costanza, Carola; Marletta, Valeria; Colecchia, Francesco Paolo; Polito, Rita; Monda, Marcellino; Messina, Giovanni; Monda, Antonietta; Mancini, Nicola; Moscatelli, Fiorenzo; Messina, Antonietta; Allocca, Salvatore; Vasco, Paride; et al. (Physical Education Theory and Methodology, 2025)
Background. Autism Spectrum Disorder (ASD) is a neurodevelopmental condition marked by social-communication difficulties, restricted interests, and motor coordination challenges. In recent years, structured physical activity programs — particularly martial arts — have gained attention as promising complementary interventions for youth with ASD. Objectives. This scoping review aimed to map and synthesize empirical evidence on martial arts interventions for individuals aged 6–18 years with ASD. Materials and methods. A systematic search of PubMed, Scopus, and Web of Science databases was conducted between January and March 2025. Results. After screening 89 records and applying rigorous eligibility filters (regarding study design, diagnosis, age range, and sample size ≥10), only two studies were included. Both studies reported statistically significant improvements in motor coordination and balance following structured martial arts programs, specifically karate kata (n = 30) and Tai Chi Chuan (n = 18). However, methodological limitations such as a lack of blinding and small sample sizes were noted. Broader literature supports additional benefits of martial arts on social engagement, executive function, emotional regulation, and parental outcomes, although the two included trials did not capture these effects. Conclusions. Despite the limited number of eligible RCTs, current evidence suggests that martial arts interventions may offer meaningful benefits across multiple developmental domains in children and adolescents with ASD. Further well-designed and rigorous trials are needed to confirm and expand these findings.